Pulmonary Hypertension in Patients with Chronic Kidney Disease on Dialysis and without Dialysis: Results of the PEPPER-Study - Pabst, Stefan; Hammerstingl, Christoph; Hundt, Felix; Gerhardt, Thomas; Grohé, Christian; Nickenig, Georg; Woitas, Rainer; Skowasch, Dirk (PLOS ONE, 2012)
Pulmonary hypertension (PH) is common in patients with dialysis-dependent chronic kidney disease and is an independent predictor of mortality. However, specific hemodynamics of the pulmonary circulation, changes induced by hemodialysis and characterization into pre- or postcapillary PH have not been evaluated in patients with chronic kidney disease. We assessed consecutive patients with end-stage chronic kidney disease in WHO FC≥II with dyspnea unexplained by other causes on hemodialysis (group 1, n = 31) or without dialysis (group 2, n = 31) using right heart catheterization (RHC). In group 1, RHC was performed before and after dialysis. In end-stage chronic kidney disease, prevalence of precapillary PH was 13% (4/31), and postcapillary PH was discovered in 65% (20/31). All four cases of precapillary PH were unmasked after dialysis. In group 2, two cases of precapillary PH were detected (6%), and postcapillary PH was diagnosed in 22 cases (71%). This is the first study examining a large cohort of patients with chronic kidney disease invasively by RHC for the prevalence of PH. The prevalence of precapillary PH was 13% in patients with end-stage kidney disease. That suggests careful screening for precapillary PH in this selected patient population. RHC should be performed after hemodialysis.